Development of vital signs monitor - Chowdhury, A.B.M. Masauddin; Wahed, Md. Abdul; Lohani, Nudrat; Chowdhury, Md. Rakibul Bari (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.